2020
DOI: 10.1128/jvi.01583-19
|View full text |Cite
|
Sign up to set email alerts
|

The Dual-Specificity Kinase DYRK1A Modulates the Levels of Cyclin L2 To Control HIV Replication in Macrophages

Abstract: HIV replication in macrophages contributes to the latent viral reservoirs, which are considered the main barrier to HIV eradication. Few cellular factors that facilitate HIV replication in latently infected cells are known. We previously identified cyclin L2 as a critical factor required by HIV-1 and found that depletion of cyclin L2 attenuates HIV-1 replication in macrophages. Here we demonstrate that cyclin L2 promotes HIV-1 replication through interactions with the dual-specificity tyrosine phosphorylation-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Tendinopathy [195] DYRK1A Human immunodeficiency virus type 1 (HIV-1) [196][197][198] DYRK1A DYRK1B Human cytomegalovirus (HCMV) [199] DYRK1B…”
Section: Dyrk1amentioning
confidence: 99%
“…Tendinopathy [195] DYRK1A Human immunodeficiency virus type 1 (HIV-1) [196][197][198] DYRK1A DYRK1B Human cytomegalovirus (HCMV) [199] DYRK1B…”
Section: Dyrk1amentioning
confidence: 99%
“…First, even if in most cases the mechanisms, underlying the pro- or antiviral activity of these kinases, were not uncovered, available data indicate that they exert their effects at multiple steps of viral life cycles ( Figure 5 ). SRPK1 and DYRK1A can control the transcription of EBOV and HIV RNAs by phosphorylating viral and cellular factors ( Booiman et al, 2015 ; Kisaka et al, 2020 ; Takamatsu et al, 2020 ). In the case of DYRK1A, this activity may also extend to other viruses thanks to its intrinsic capacity to phosphorylate the host RNA polymerase II CTD and modulate its activity.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the consequences of this polymorphism on the enzyme were not investigated, subsequent studies showed that DYRK1A can downregulate HIV-1 transcription likely by phosphorylating NFAT, a transcription factor of the HIV-1 LTR, and by inducing its translocation into the cytoplasm ( Booiman et al, 2015 ). Further studies also pointed to a role of DYRK1A in the inhibition of HIV-1 replication in macrophages by phosphorylating Cyclin L2 and inducing its degradation ( Kisaka et al, 2020 ). The antiviral effect of DYRK1A was shown to occur at the transcriptional level.…”
Section: Interplay With Viral Replicationmentioning
confidence: 99%
“…The LCMV attachment factor DAG1 was detected, albeit at a lower enrichment score. Additional host factors that were significantly enriched include those described for other viral infections, such as negative-stranded RNA virus vesicular stomatitis virus (VSV) (ARFRP1, SYS1, YKT6) and the human immunodeficiency virus (HIV) (SRP14, DYRK1A, IL2RA) (33)(34)(35)(36)(37).…”
Section: Crispr Ko Screens Identify Host Factors For Lcmv Infectionmentioning
confidence: 99%